3D position determination in monolithic crystals coupled to SiPMs for PET. (27th April 2016) - Etxebeste, Ane; Barrio, John; Muñoz, Enrique; Oliver, Josep F; Solaz, Carles; Llosá, Gabriela
Abstract: The interest in using continuous monolithic crystals in positron emission tomography (PET) has grown in the last years. Coupled to silicon photomultipliers (SiPMs), the detector can combine high sensitivity and high resolution, the two main factors to be maximized in a positron emission tomograph. In this work, the position determination capability of a detector comprised of a 12 × 12 × 10 mm 3 LYSO crystal coupled to an 8 × 8 -pixel array of SiPMs is evaluated. The 3D interaction position of γ -rays is estimated using an analytical model of the light distribution including reflections on the facets of the crystal. Monte Carlo simulations have been performed to evaluate different crystal reflectors and geometries. The method has been characterized and applied to different cases. Intrinsic resolution obtained with the position estimation method used in this work, applied to experimental data, achieves sub-millimetre resolution values. Average resolution over the detector surface for 5 mm thick crystal is ∼0.9 mm FWHM and ∼1.2 mm FWHM for 10 mm thick crystal. Depth of interaction resolution is close to 2 mm FWHM in both cases, while the FWTM is ∼5.3 mm for 5 mm thick crystal and ∼9.6 mm for 10 mm thick crystal.